Coffee intake may promote sudomotor function activation via the contribution of caffeine - Kwon, Ryeo-Won; Park, Jin-Sun; Lee, Ha-Gyoung; Park, Jong-In; Choo, Eon-Ah; Lee, Seung-Jea; Lee, Jeong-Beom (Frontiers in Nutrition, 2022)
The purpose of this study was to determine whether drinking coffee with caffeine accelerates the sympathetic response to acetylcholine (ACh). Tests were performed twice at 1-week intervals following the intake of coffee. Subjects were randomly divided into two groups: Group A was administered 16 fluid oz of water (CON), while Group B was given 16 fluid oz of coffee (Coffee). After 1 week, Group A was administered 16 fluid oz of coffee (Coffee), while Group B was given 16 fluid oz of water (CON). The quantitative sudomotor axon reflex test (QSART) was performed after intake of coffee and water and a 40 min break. QSART with iontophoresis and 10% ACh was performed to determine axon reflex (AXR) mediated with and without iontophoresis [AXR (1) and AXR (2), respectively], and directly activated sweating (DIR). The sweat onset time of the AXR was shorter in the Coffee compared with the CON (p < 0.05). The sweat rates in AXR (1) AXR (2) and DIR were significantly higher in the Coffee than in the CON (p < 0.05, p < 0.05, p < 0.01, respectively). In addition, the Coffee showed significantly higher density of activated sweat glands and activated sweat gland output than the CON (p < 0.05, p < 0.01, respectively). The overall results of this study showed that coffee intake could stimulate higher activation in both AXR and DIR sweat responses. In addition, it has been shown that coffee intake can improve sweating sensitivity by the contribution of caffeine contained in coffee. This suggests that other compounds in coffee may not inhibit the sympathetic response to ACh. Therefore, coffee may be clinically worth considering as a supplement for activation of sudomotor function and increase of thermogenesis.